A primitive equation spectral model for study of planetary-scale atmospheric flow - BEDI, HS (MAUSAM, 1985)
The developments in numercial modelling for the atmosphere in recent years have shown that the spectral models are well suited for general circulation studies of the planetary-scale atmosphere. The use of transform method developed during last decade has made the spectral models comparable in computational speed with the grid point models. A global primitive equation model using spectral formulation is under development in the India Meteorological Department. The spectral representation is in terms of a truncated series of surface spherical harmonic functions. The computational facllitiesavaila1Jle at present do not perlt1it the development of a high-resolution model. The horizontal resolution, therefore, is limited to six Fourier waves in the zonal direction, and six zeros of Legendre functions in the meridional direction. In the vertical, the model has three layers in sigma coordinate. The model is in Its early stage of development. The model formulation, the results of some experiments performed with It and the future development plans are discussed in this paper.